NONSTANDARD GAMMA-GAMMA-]L+L- PROCESSES IN RELATIVISTIC HEAVY-ION COLLISIONS - Almeida, L. D.; Natale, A. A.; Novaes, Sérgio Ferraz [UNESP]; Eboli, OJP (American Physical Soc, 1991)
We study lepton pair production in heavy-ion collisions with emphasis on nonstandard contributions to the QED subprocess gamma-gamma --> l+l-. The existence of compositeness of fermions and/or bosons can be tested in this reaction up to the TeV mass scale. We show that for some processes the capabilities of relativistic heavy-ion colliders to disclose new physics surpass the possibilities of e+e- or ppBAR machines. In particular, spin-zero composite particles which couple predominantly to two photons, predicted in composite models, can be studied in a broad range of masses.